Método para gestão de ordens de produção em processos de corte, conformação e usinagem, em uma indústria de implementos agrícolas - Hoose, Anderson (2013)
The great diversification and customization of products led agricultural implements companies to broaden their product line, considering this creates the need to reduce inventories of components in process and improve control over the flow of production, aiming mainly cater satisfactorily parts designed to welding and assembly lines. It is within this context that the present paper presents a methodology for controlling the flow of parts that pass through process which precede welding and assembly operations, aiming at the level of inventory between stamping and machining operations and for a better direct the flow of production, with the implementation of a warehouse of parts in process, where after the first operation, the parts go to the warehouse and wait the clearance for delivery to the following machines, following the priority criterion and machine capacity avaliable, placing the parts in a waiting area near the machines that will perform the second operation. In another step, for certain items machined, will program the optimal amount of parts for better care of weld lines, aiming to implement a hybrid system of parts production. Having a step of feedback information in the warehouse for parts with the first sector cutting operation, thus enabling a better controlled process parts in accordance with the production rate and cycle time. Such measures will be possible for the application to the redefinition of some activities related to the Departament of Planning and Production Control which in turn goes plan the manufacture of parts and determines the quantities of items to be manufactured and together with the goal of Direction production to be achieved by the company